Additive engineering for highly efficient organic–inorganic halide perovskite solar cells: recent advances and perspectives. Issue 25 (5th June 2017) - Li, Taotao; Pan, Yufeng; Wang, Ze; Xia, Yingdong; Chen, Yonghua; Huang, Wei
Abstract : Recent advances in additive engineering for improving the perovskite morphology, charge transport, and excitonic and optical properties have been reviewed. Abstract : Organic–inorganic halide perovskite solar cells have recently attracted much attention due to their low-cost fabrication, flexibility, and high efficiency. The power conversion efficiency achieved with such cells was over 22% in 2016 from an initial 3.81% in 2009, highlighting how the cells are now benefiting from the highly optimized morphology of perovskite films. To date, a great number of approaches have been done to improve the morphology of perovskite films, in which additives play an important role in perovskite crystal growth and in the dynamics of the crystallinity, and thus the performance of perovskite solar cells. Herein, we review the recent progress on additives, such as polymers, fullerene, metal halide salts, organic halide salts, inorganic acids, solvents, and nanoparticles, in improving the morphology of perovskite films in terms of the crystal growth, crystallization kinetics, and device performance. We also discuss the importance of further understanding the fundamental homogeneous nucleation process by the use of additives. Further innovation in terms of the additives could help to further develop high-performance devices with long-term stability for future practical applications of perovskite solar cells.